EFL teacher's knowledge toward their current practices - Mohd. Yusof, Sanitah (2015)
There are many factors which influence the process of teaching English as a foreign language. One of the most influential in the process of teaching English is teachers’ knowledge of teaching English. Knowledge of teaching English plays an important role in teachers’ effectiveness and their choice of instructional practices. The total sampling of 133 Indonesian EFL teachers with different years of teaching experiences were participated in this study. After obtaining the raw data, the SPSS software (version 20) was used to analyze the data. The findings showed that the most dominant element of EFL teachers’ knowledge of teaching English is teaching skills, and there is a significant influence of EFL teachers’ teaching skills to their practices of teaching English. This research also indicated that there are no significant differences among the years of EFL teachers’ teaching experiences toward their knowledge of teaching English.